Night - Wiesel, Elie, 1928-2016.; Rodway, Stella; Mauriac, Francois, 1885-1970; Brown, Robert McAfee, 1920-2001 (New York : Bantam Books, 1982)
"Night--A terrifying account of the Nazi death camp horror that turns a young Jewish boy into an agonized witness to the death of his family ... the death of his innocence ... and the death of his God. Penetrating and powerful, as personal as The diary of Anne Frank, Night awakens the shocking memory of evil at its absolute and carries with it the unforgettable message that this horror must never be allowed to happen again"--Provided by publisher
Accelerated Reader
Translation of French version of: Un di velt hot geshvign.
Originally published in Yiddish in a more expanded version, under title: Un di velt hot geshvign.
Keywords: Wiesel, Elie, -- 1928-2016 -- Childhood and youth; Jews -- Romania -- Sighet -- Biography; Holocaust, Jewish (1939-1945) -- Romania -- Sighet -- Personal narratives; Authors, French -- 20th century -- Biography; Jewish authors -- 20th century -- Biography; Holocaust -- history; Concentration camps -- History; Literature, modern; Holocaust -- Europe -- History -- Personal narratives; Concentration camps -- Europe -- History -- Personal narratives; Sighet (Romania) -- Biography; Europe